2007
DOI: 10.1158/1535-7163.mct-06-0729
|View full text |Cite
|
Sign up to set email alerts
|

Levels of p27kip1 determine Aplidin sensitivity

Abstract: Aplidin (plitidepsin) is a novel anticancer drug isolated from the marine tunicate Aplidium albicans. Aplidin shows potent antitumor activity in preclinical models against a wide variety of human tumors. Aplidin is currently in phase II clinical trials in a variety of solid tumors and hematologic malignancies. Moreover, clinical studies of Aplidin in combination with other agents are ongoing because it generally lacks cross-resistance with other known cytotoxic drugs. The mode of action of Aplidin in tumor cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…34 One day before transfection, 2 Â 10 4 MEL HO human melanoma cells per well were seeded in 6-well plates containing 2 ml of normal growth medium. Total cell number was determined the day before the transfection.…”
Section: Small Interfering Rna Gene Silencing Methodsmentioning
confidence: 99%
“…34 One day before transfection, 2 Â 10 4 MEL HO human melanoma cells per well were seeded in 6-well plates containing 2 ml of normal growth medium. Total cell number was determined the day before the transfection.…”
Section: Small Interfering Rna Gene Silencing Methodsmentioning
confidence: 99%
“…We carried out this method according to the manufacturer's instructions (Invitrogen, Madrid, Spain) and according to a previous study [34]. One day before transfection, 2×10 4 cells per well from the BE-13 and SD-1 human leukemia cell lines were seeded in 6-wells plates containing 2 ml of normal growth medium.…”
Section: Small Interfering Rna (Sirna) Gene-silencing Methodsmentioning
confidence: 99%
“…Moneo and colleagues reported that the levels of p27 sensitize sarcoma cell lines to Aplidin, a macrocyclin depsipeptide showing antitumor activity in various human tumors (25). Higher p27 levels were recently found to be associated with improved response of breast cancer cell lines to 2 rapalogs, temsirolimus and everolimus (RAD001; ref.…”
Section: Introductionmentioning
confidence: 99%